ANALISIS KEMAMPUAN BERPIKIR KREATIF DALAM PEMECAHAN MASALAH DITINJAU DARI PERBEDAAN GENDER - Erlinawaty Simanjuntak; Yasifati Hia; Nurliani Manurung (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
This study aims to look at how the role of gender in the creative thinking process of students, especially in solving math problems. This research is included in exploratory research with a qualitative approach. The qualitative approach was chosen because in this study the main data were written and/or spoken words. The subjects of this research are 1 semester students of mathematics education study program. The main instrument is the researcher himself while the assistive instrument uses problem solving tests, interview guidelines, and recording aids. The results of the analysis and discussion that have been done show that students who have different levels of thinking ability will also have different levels of creative thinking. Gender also influences the results of creative thinking, where in the subject of this study, the creative thinking ability of female students is better than that of men. Keywords: Creative Thinking Ability, Problem Solving, Gender Differences